The Impact of COVID-19 on Economic of Oman and Omani Customer’s Behaviour - Said Ambu Saidi, Khaloud Salim; Abu Kausar, Mohammad; M. Elshaiekh, Nour-Eldin (International Journal of Scientific Research and Management (IJSRM), 2021)
Abstract— The emerging corona virus (Covid-19) has become at the forefront of the scene around us around the world, after the disease has swept all over the earth, causing high numbers of deaths and infections, and it continues to expand terribly across countries without stopping or finding a drug that can stop it finally in an effective form yet. For sure the emergence and spread of the virus in this rapid way has effectively and strongly affected people, commerce and industries. Many researchers who were interested in the field of e-commerce around the world are more intensive to learn about the impact that the emergence of the emerging corona virus (Covid-19) has on the economic around the world, and economics of Oman in depth and whether this effect was negative or positive, and what are the aspects of Impact. The main objective of this research paper is to investigate in deep through reviewing several studies, the effect of corona virus in economics of Oman and Omani consumer’s behavior as well as the aspects of the change that occurred in the behavior of Omani consumers as a result of this virus.